Predictors of atrial fibrillation occurrence in patients with hypertrophic cardiomyopathy. (25th November 2020) - Castelo, A; Rosa, S; Fiarresga, A; Marques, H; Portugal, G; Cunha, P; Ferreira, V; Bras, P; Goncalves, A; Oliveira, M; Ferreira, R
Abstract: Introduction: Patients with hypertrophic cardiomyopathy (HCM) are at increased risk of dysrhythmias, especially atrial fibrillation (AF). Purpose: The aim of this study was to evaluate the incidence of AF in HCM patients (P) and to determine predictors of AF. Methods: Retrospective analysis of HCM P at a single tertiary center. Baseline clinical, echocardiographic and cardiovascular magnetic resonance (CMR) characteristics were collected. On follow up AF was identified by electrocardiogram and/or 24 hours Holter monitoring. Results: 61P (59% male) were included, with a mean age of 58±2 years. 27.9% had angina (all of them CCS 2), 34.4% were in NYHA II and 14.8% in NYHA III, 8.2% had syncope and 39.3% had palpitations. A family history of sudden cardiac death (SCD) or cardiomyopathy was present in 40.4% of the cases. The mean HCM risk SCD score was 3.35±0.28%. On echocardiography left atrium (LA) diameter was 44.86±0.87mm, LA volume (LAvol) was 89.97±5.39mL (indexed LAvol 46.05±2.55mL/m 2 ), interventricular septum (IVS) was 16.83±0.663mm, left ventricle (LV) mass was 290.94±13.897g and maximum wall thickness (MWT) was 20.59±0.596mm. 77% P had LA enlargement. 88.5%P had late gadolinium enhancement (LGE) in CMR with a median number of 5±7 segments involved. AF developed in 23P (37.7%), with a mean age of 58±3 years. Predictors of AF development were NYHA III (p=0.007), risk score (p=0.007), LA diameter (p=0.007), LAvol (p=0.005) and indexed LAvol (p=0.002), MWT (p=0.0015), LGE in more than 5 segments (p=0.029) and LGE in the inferior basal and inferior median IVS (p=0.033 and p=0.042). The only independent predictor was LAvol (p=0.0012), with an area under the curve of 0.755 and a cut off of 85.9mL being the best predictor (p=0.004). Combining LAvol >85.9mL with LGE involving >5 segments and LAvol >85.9mL with LGE in inferior basal IVS (IBIVS) a statistically significant difference between groups was achieved (p=0.009 in the combined predictor LAvol + LGE >5 segments and p=0.002 in the combined predictor LAvol + LGE in IBIVS) (figure 1 and figure 2). In a multivariable analysis including these 2 combined predictors and LAvol alone the only independent predictor was the combination of LAvol + IBIVS involvement. Conclusion: AF is frequent in patients with HCM and develops in younger ages than in general population. NYHA III, risk score, LA diameter, LAvol, MWT, LGE >5 segments and LGE in IBIVS and in IMIVS were predictors of AF, with LAvol being the independent predictor. The combination of LAvol with LGE >5 segments and LAvol with LGE in IBIVS presented stronger predictor value comparing with these characteristics alone. Funding Acknowledgement: Type of funding source: None